The Welfare Effects of Mandatory Reemployment Programs: Combining a Structural Model and Experimental Data - Jonas Maibom (Institute of Labor Economics (IZA), 2021)
This paper estimates a structural model of job search which accounts for utility costs and benefits linked to mandatory reemployment programs. The estimation uses data from a randomized experiment which generates exogenous variation in the threat of program participation. I use the compensating variation (CV) as a measure of the impact of the experimental treatment on worker welfare, the welfare costs. I find that participants would be willing to give up 1.5-1.7 weeks of UI on average to avoid participation in the program, although the program has a positive effect on the job finding rate. Welfare costs vary across workers and are found to be larger for workers with weaker employment prospects. Overall, the analysis shows that the welfare costs are substantial and therefore necessary to take into account when evaluating the case for mandatory reemployment programs.
Keywords: C9; I3; J64; J65; J68; 330; active labor market program; activation; job search; unemployment